Overproduction, purification, and ATPase activity of the Escherichia coli RuvB protein involved in DNA repair. - Iwasaki, H (1989)
The ruvA and ruvB genes of Escherichia coli constitute an operon which belongs to the SOS regulon. Genetic evidence suggests that the products of the ruv operon are involved in DNA repair and recombination. To begin biochemical characterization of these proteins, we developed a plasmid system that overproduced RuvB protein to 20% of total cell protein. Starting from the overproducing system, we purified RuvB protein. The purified RuvB protein behaved like a monomer in gel filtration chromatography and had an apparent relative molecular mass of 38 kilodaltons in sodium dodecyl sulfate-polyacrylamide gel electrophoresis, which agrees with the value predicted from the DNA sequence. The amino acid sequence of the amino-terminal region of the purified protein was analyzed, and the sequence agreed with the one deduced from the DNA sequence. Since the deduced sequence of RuvB protein contained the consensus sequence for ATP-binding proteins, we examined the ATP-binding and ATPase activities of the purified RuvB protein. RuvB protein had a stronger affinity to ADP than to ATP and weak ATPase activity. The results suggest that the weak ATPase activity of RuvB protein is at least partly due to end product inhibition by ADP.